The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.04.20.440612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enrichment analyses identify shared associations for 25 quantitative traits in over 600,000 individuals from seven diverse ancestries

Abstract: Since 2005, genome-wide association (GWA) datasets have been largely biased toward sampling European ancestry individuals, and recent studies have shown that GWA results estimated from European ancestry individuals apply heterogeneously in non-European ancestry individuals. Here, we argue that enrichment analyses which aggregate SNP-level association statistics at multiple genomic scales—to genes and pathways—have been overlooked and can generate biologically interpretable hypotheses regarding the genetic basi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 191 publications
(415 reference statements)
0
5
0
Order By: Relevance
“…As discussed in ref. 43 , it is more ideal to consider the ancestrytrait-specific Bonferroni-corrected significance threshold. In our study, we only consider the Taiwanese population, and the maximum number of tested SNPs is 5,981,581 for all traits.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in ref. 43 , it is more ideal to consider the ancestrytrait-specific Bonferroni-corrected significance threshold. In our study, we only consider the Taiwanese population, and the maximum number of tested SNPs is 5,981,581 for all traits.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our method assumes only that causal genes for complex traits are shared across ancestries while making no assumptions on underlying eQTL architectures across ancestries. This is an important feature of our method considering recent findings that SNP-level replication across genetic ancestries is weaker than gene-level replication 36 , and that only ∼30% of SNP-gene expression associations are shared between European- and African-American ancestry 39 . Through extensive simulations, we demonstrate that MA-FOCUS’ ability to identify causal genes is superior to baseline approaches and is robust to data-dependent limitations (see Methods ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, MA-FOCUS assumes only that the causal genes for a focal trait or disease are shared across ancestries. It is expected that gene-level effects are likely more transferable across ancestry groups than SNP-level effects as genes are inherently a more meaningful biological unit 36 . As a result, MA-FOCUS leverages cross-ancestry heterogeneity in LD patterns and eQTL associations to identify causal genes with improved precision and accuracy when compared with alternative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with HBA1C readings of 42-48 mmol/mol, a range associated with prediabetes, were not included in the analysis. Ancestry Mismatch Experiment: Individuals were first divided on the basis of ancestry, as in Smith et al 2021, identifying 349,411 individuals of self-identified European descent, and 4,967 individuals of African descent. The latter of which were identified both by self-identification and by an ADMIXTURE analysis as described in (Smith et al 2021).…”
Section: Unknown Class Example: Wheat Seeds Datasetmentioning
confidence: 99%
“…Ancestry Mismatch Experiment: Individuals were first divided on the basis of ancestry, as in Smith et al 2021, identifying 349,411 individuals of self-identified European descent, and 4,967 individuals of African descent. The latter of which were identified both by self-identification and by an ADMIXTURE analysis as described in (Smith et al 2021). Applying the HBA1C filter described above resulted in 8,631 individuals in the European/elevated cohort, 268 individuals in the African/elevated cohort, 243,283 individuals in the European/normal cohort and 2,532 individuals in the African/normal cohort.…”
Section: Unknown Class Example: Wheat Seeds Datasetmentioning
confidence: 99%